the HUBUNGAN KEBIASAAN KOMSUMSI MAKANAN CEPAT SAJI DENGAN RISIKO PENYAKIT JANTUNG PADA REMAJA PUTRI DI SMA NEGERI 13 BOMBANA KECAMATAN MATAOLEO KABUPATEN BOMBANA - ani, hasni; asi, melania; Kartini, Kartini; Hikmandayani, Hikmandayani (Poltekkes Kemenkes Kendari, 2025)
Introduction: Heart disease is one of the deadliest non-communicable diseases (NCDs) worldwide. This disease affects not only adults and the elderly but is also beginning to show increasing prevalence among young people, including adolescents. The purpose of this study was to determine the relationship between fast food consumption habits and the risk of heart disease in adolescent girls at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. Methods: This study was quantitative and designed using an observational cross-sectional approach. The population was all 187 adolescent girls at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. The sample was 65 adolescents at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. The test tool used in the bivariate analysis was the Chi-square test. Results: Of the 65 respondents, the habit of consuming fast food among adolescent girls was mostly in the low category, with 38 people (58.4%), and the risk of heart disease among adolescent girls was mostly in the no-risk category, with 45 people (69.2%). There is a relationship between the habit of consuming fast food and the risk of heart disease among adolescents at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency (x2 = 15.276; p-value = 0.000). Conclusion: There is a relationship between the habit of consuming fast food and the risk of heart disease among adolescent girls at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency.